THE VARIABILITY OF THE ESSENTIAL OIL COMPOSITION IN THE SAGE COLLECTION OF THE GENEBANK GATERSLEBEN - Lamien-Meda, A.; Schmiderer, C. L.; Lohwasser, U.; Börner, A.; Franz, Ch; Novak, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Genebanks are valuable resources for ex-situ conservation and breeding of economic plants and wild plant relatives. Analysing plant secondary compounds of such collections delivers useful information about the variability (heterogeneity) in the collection and enables plant breeders to pre-select accessions when breeding for specific plant secondary compounds like essential oil content and/or composition. For garden sage (Salvia officinalis L.), 10 individual plants of each of the 19 accessions available in the genebank were analysed for their essential oil content and composition. The essential oil content was in the range of 0.8% to 2.4%. The essential oil composition was comparable to results already published with the exception of two accessions, which were very low in Î±-thujone (3%) and Î²-thujone (<1%), representing a new chemotype in Salvia officinalis.